Efficacité De La Pollinisation Entomophile Du Palmier A Huile Dans Les Plantations Du Sud-Ouest Et Du Sud-Est De La Côte d’Ivoire - Malanno, Kouakou; Adelphe, Hala Kinampinan; N’klo, Hala; Mamadou, Dagnogo (European Scientific Journal, ESJ, 2018)
Low fruit set rates in oil palm plantations may be related to inadequate entomophilous pollination. The objective of this study was to follow the variations of fruit set and to determine its relationships with the entomofauna visiting inflorescences at La Mé, Grand-Béréby and Iboké in Côte d’Ivoire. Densities of the insects were followed out on male and female inflorescences during 12 months. The fruit set rate was also monitored over the same period on young bunches. The results showed that pollination is provided by Elaeidobius kamerunicus, Elaeidobius plagiatus, Elaeidobius singularis, Elaeidobius subvittatus, Microporum congolense, Microporum dispar and Atheta burgeoni. At La Mé, the fruit set rate was negatively correlated with the damage of Prosœustus spp (r = -0.43, p = 0.01) and positively with the abundance of E. kamerunicus and E. plagiatus on female flowers (respectively: r = 0.60, p = 0.002 and r = 0.47, p = 0.020). At Grand-Béréby, it is negatively correlated with the damage of Prosœustus spp (r = -0.42, p = 0.01). At Iboké, positive correlations were observed with the density of E. subvittatus (r = 0.40, p ˂ 0.001), M. congolense (r = 0.41, p = 0.046), M. dispar (r = 0.57, p = 0.004) and A. burgeoni (r = 0.65, p ˂ 0.001). This study highlighted the necessity to manage the populations of pollinators and the inflorescences pest insects to improve the production of oil palm in Côte d'Ivoire.